(untitled) (Journal of the College of Basic Education, 2022)
The significance of the words has a strong and great relationship with the psychological state that the individual is going through, such as anger, sadness, joy, etc., of the feelings that a person experiences. Every situation that a person goes through makes him choose words that express the greatness and intensity of the situation in him. The expressions of sadness are different from joy, and the expressions of distress are different from prosperity, and other feelings and emotions are represented through words to reach the recipient, confirming the sender’s feeling and confirming it. All of this is confirmed by the Holy Qur’an in many places in the Qur’anic verses. The Qur’an has taken care of man in all of his states, and he expressed that through the different expressions and their connotations. This confirms the observance of the human soul, especially the groups that were marked by weakness, the parents, the orphan, the woman, and everything related to mercy, as will be noted in the following pages